2020
DOI: 10.1016/j.heliyon.2020.e04974
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production – producing microorganisms and substrates sources-state of art

Abstract: Lactic acid is an organic compound produced via fermentation by different microorganisms that are able to use different carbohydrate sources. Lactic acid bacteria are the main bacteria used to produce lactic acid and among these, Lactobacillus spp. have been showing interesting fermentation capacities. The use of Bacillus spp. revealed good possibilities to reduce the fermentative costs. Interestingly, lactic acid high productivity was achieved by Corynebacterium glutamicum and E. coli, mainly after engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(162 citation statements)
references
References 387 publications
7
99
0
2
Order By: Relevance
“…Several authors have reported data using different Lactobacillus sp. strains through both batch and fed-batch fermentation configuration [ 46 , 60 , 61 ]. However, the lactic acid production by Carnobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported data using different Lactobacillus sp. strains through both batch and fed-batch fermentation configuration [ 46 , 60 , 61 ]. However, the lactic acid production by Carnobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the best VP (1.64 g/l.h; 1.65 g/l.h and 1.65 g/l.h) obtained in the PIB, PAB and BAB respectively are much important than the one that obtained (0.121 g/l.h) by Ali et al (2012) who, in the course of their work, produced LA from mango peel waste using a factorial experiment. From these observations, it follows that the acidifying power could be dependent on the strain and experimental conditions; similarly, it would be equally influenced by the duration of fermentation and the nature of the substrate present in the production medium (Wee et al, 2006;Battula et al, 2018;Abedi and Hashemi, 2020). However, the chemical composition of the fruit by-products used during fermentation, the nature of the treatments to which the different carbohydrate substrates are subjected, the composition of the fermentation medium, would influence the amount of lactic acid produced and would be responsible for the differences observed between our acidity values and those in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, this fermentation process involves relatively expensive substrates such as glucose, sucrose, lactose and maltose, hence the need for research for raw materials that are less expensive to be used in its production (Richard, 2015;Battula et al, 2018). Thus it is in this context that efficient LA production has been reported from various alternative substrates such as molasses, hydrolysate newspaper, whey, Cassava bagasse, starch, sweet sorghum juice and lignocellulose biomass (Wee et al, 2006;Zhang and Vadlani, 2014;Abedi and Hashemi, 2020). As well as the derived by-products mentioned above, by-products from households and tropical fruit (orange, mango, papaya, banana, and pineapple) processing industries, due to their high carbohydrate composition (Phatcharaporn et al, 2009;Chukwuka et al, 2013;Maria et al, 2014), could be potential substrates for LA production by appropriate microbial strains and thus reducing the cost linked to the LA production by this fermentation pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic Acid (LA) is industrially manufactured through the anaerobic fermentation of agricultural products, such as wheat, potatoes, sugar-beets, corn and sugarcane molasses [ 23 ]. Starch and sugars are converted to lactic acid through bacterial fermentation with the use of Lactic Acid Bacteria (LAB) such as Lactobacillus casei , Lactococcus lactis Lactobacillus acidophilus , Lactobacillus delbrueckii subsp.…”
Section: Synthesis Of Monomersmentioning
confidence: 99%